Enhanced electrochromic coloration in Ag nanoparticle decorated WO3 thin films - Kharade, Rohini R.; Mali, Sawanta S.; Patil, Satish P.; Patil, Kashinath R.; Gang, Myong G.; Patil, Pramod S.; Kim, Jin H.; Bhosale, Popatrao N. (Electrochimica Acta, 2013)
WO3/Ag composite thin films were prepared by microwave assisted sol-gel synthesis (MW-SGS) of WO3 followed by vacuum evaporation of Ag nanoparticles and their enhanced electrochromic coloration was investigated. The composition and morphology of WO3 thin films with different thickness of Ag layer obtained by vacuum evaporation were investigated. Distinct plasmon absorption bands of Ag nanoparticle thin films were obtained. The optical band gap energy of WO3/Ag films decreased with increasing the Ag layer thickness. The surface of these films has been examined using X-ray photoelectron spectroscopy (XPS) to gain information about the chemical states of species present at surfaces. Experimental results indicated that the conductivity of the films increased after surface modification by Ag layer. To investigate the origin of enhanced electrochromic absorption in optical properties, working electrode consisting of WO3/Ag thin film was used and observed the optical properties during electrochemical reaction. It was found that composite electrode shows enhancement in electrochromic properties in terms of optical modulation (Delta OD) and coloration efficiency (eta). (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Ag2WO4; CIE coordinates; Electrochromism; SPR; WO3/Ag composite thin films

Partially bio-based triarylamine-containing polyimides: synthesis, characterization and evaluation in non-volatile memory device applications - Chatterjee, Deepshikha; Jadhav, Uday A.; Javaregowda, Bharathkumar H.; Dongale, Tukaram D.; Patil, Pramod S.; Wadgaonkar, Prakash P. (European Polymer Journal, 2021)
A new triarylamine-containing diamine, viz. 4, 4'-diamino-4 `' pentadecyltriphenylamine was synthesised starting from cashew nut shell liquid (CNSL) - a non-edible by-product of cashew processing industry. Three new partially bio-based triarylamine-containing polyimides were synthesised by one-step high temperature solution poly-condensation of 4, 4'-diamino-4 `' pentadecyltriphenylamine with aromatic dianhydrides, namely, 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA), 4,4'-oxydiphthalic anhydride (ODPA) and 4,4'-(hexa-fluoroisopropylidene) diphthalic anhydride (6-FDA). Polyimides were determined to be of reasonably high molecular weights as inherent viscosity and number average molecular weights (M-n, Polystyrene standard) values were in the range 0.54-0.60 dL g(-1) and 26,800-43,500 g mol(-1), respectively. Polyimides exhibited excellent solubility in common organic solvents and film-forming nature along with reasonably good thermal properties as indicated by temperature for 10% weight loss (T-10) and glass transition temperatures (T-g) which were in the range 418-447 and 165-225 degrees C, respectively. The optical and electrochemical band-gap values were in the range of 1.95-1.98 eV and 1.671-1.745 eV, respectively. Among triarylamine-containing polyimide devices, BPDA-based device showed acceptable current-voltage and non-volatile memory properties such as the endurance of 500 cycles and 1000 s of retention time. The conduction mechanism developed in the memory devices was also explored and was found to follow Ohmic and Schottky conduction mechanisms.
Keywords: Bio-based polyimides; CNSL; Memory device; pentadecyl; Triarylamine